A integração entre o Sistema Nacional de Atendimento Socioeducativo (SINASE) e o Sistema Único da Assistência Social (SUAS) na promoção dos direitos de adolescentes em cumprimento de medida socioeducativa - Souza, Adilson Fernandes de (2010)
The main goal of this study is to verify the integration between the National System of Socioeducative Support (SINASE, in Portuguese) and the Unique System of Social Assistance (SUAS, in Portuguese) in the care of teenagers receiving socioeducative support under arrest and in the open system. For this evaluation I started with a historic recall of the social attention given to poor children and teenagers, abandoned and with infractional practice, what led me to realize the on going practices that disconsider the rights of people still in development. Those rights were assured only in 1990 with the advent of the Child and Teenager Law (ECA, in Portuguese Law 8.069, 07/13/1990). I have also analyzed the prison system for adults, which certainly influences until the present days the socioeducative system destinated to teenagers and minors envolved with delicts. This research process has been performed in the city of Bragança Paulista, where we can find an unity of the Socioeducative Support Center for Teenagers Foundation (Fundação CASA-SP, in Portuguese) In this place, the socioeducative support in an open system is under the management of the city, according with the recommended by the Child and Teenager Law (ECA), the National System of Socioeducative Support (SINASE) and the Unique System of Social Assistance (SUAS)